MODUL PEMBELAJARAN MENULIS CERITA PADA SISWA SEKOLAH DASAR - She Fira Azka Arifin; Wahyu Sukartiningsih; Titik Indarti (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
Learning to write stories is one of the competencies taught to elementary school students. Therefore we need an appropriate learning module in the learning process. This research uses a literature study method which is taken from relevant previous research. Literature retrieval techniques based on keywords, year of publication, and research problems. Keywords that are the focus of the search on google scholar are the learning module to write stories for elementary school students with the publication year between 2015 - 2021. The literature study aims to find and analyze the learning module to write short stories in elementary school students so that the learning model found can be known, selected, and applied to elementary school students in accordance with the characteristics and needs of students. The results of this study obtained as many as 7 literature. The conclusion obtained in this study is that there are several modules used in short story writing. Among them include an enrichment module for writing children's stories with character values based on CLIL, a learning module for reading comprehension of adventure story texts, a module for writing creative stories, a module that is oriented towards a scientific approach to learning narrative writing.